1985
DOI: 10.1128/mcb.5.7.1707
|View full text |Cite
|
Sign up to set email alerts
|

Neoplastic transformation of normal and carcinogen-induced preneoplastic Syrian hamster embryo cells by the v-src oncogene.

Abstract: The ability of cloned Rous sarcoma virus (RSV) DNA encoding the v-src oncogene to neoplasticafly transform normal, diploid Syrian hamster embryo (SHE) cells was examined. Transfection of RSV DNA into early passage SHE cells resulted in a low but significant number of tumors when treated cells were injected into nude mice. Tumors formed with a low frequency (two tumors out of ten sites injected) and only after a long latency period (14 weeks). In contrast to the normal SHE cells, several different carcinogen-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
7
0

Year Published

1986
1986
1997
1997

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 29 publications
(33 reference statements)
2
7
0
Order By: Relevance
“…To our knowledge, no other studies have examined the direct role of cellular age in oncogene transformation of nonestablished cells. However, a number of papers have reported on the ability of various oncogenes (7,34,50,66), including v-src (15,23), to transform early-passage cells, findings which are consistent with the results obtained here. Furthermore, early work by Newbold and Overell (48) demonstrated that cellular senescence is a critical determinant of resistance of Syrian hamster fibroblasts to transformation by an activated ras gene, and more recent experiments by Newbold et al have provided further evidence for a role of cellular im-mortality in myc-ras transformation of these cells (47).…”
Section: Figsupporting
confidence: 91%
See 1 more Smart Citation
“…To our knowledge, no other studies have examined the direct role of cellular age in oncogene transformation of nonestablished cells. However, a number of papers have reported on the ability of various oncogenes (7,34,50,66), including v-src (15,23), to transform early-passage cells, findings which are consistent with the results obtained here. Furthermore, early work by Newbold and Overell (48) demonstrated that cellular senescence is a critical determinant of resistance of Syrian hamster fibroblasts to transformation by an activated ras gene, and more recent experiments by Newbold et al have provided further evidence for a role of cellular im-mortality in myc-ras transformation of these cells (47).…”
Section: Figsupporting
confidence: 91%
“…Transgenic mice bearing the activated c-neu oncogene develop mammary neoplasias in a single-step fashion (46), and retroviral delivery of v-Ha-ras to the rat mammary gland in vivo results in the emergence of multiple adenocarcinomas (75). Furthermore, a syndrome resembling chronic myelogenous leukemia is observed in mice after bone marrow infection with a retrovirus carrying the bcr-abl gene (8), and a number of studies have reported that primary cell cultures can be transformed by a single oncogene, like v-src (15,23), activated ras (10,26,34,50,52,66,68,78), EB2 of Epstein-Barr virus (7), eIF-4E (36), and simian virus 40 (SV40) large T (SV-LT). (6,72).…”
mentioning
confidence: 99%
“…Furthermore, carcinogen-induced immortality of these cells has been shown to be an important step in the tAg+ hybrid frequency was determined from the number of colonies growing in agar containing selective (HAT/ouabain) medium at 3 weeks after selection. neoplastic progression of these and other cells (1,6,17,29,30). However, several lines of evidence indicate that an additional change is required for neoplastic transformation.…”
Section: Resultsmentioning
confidence: 99%
“…p60 "-~ also transforms rodent cell lines (5,24,27), yet it is not clear whether it can efficiently convert primary cultures of mammalian cells. Gilmer et al (17) reported that v-src transforms Syrian hamster embryo cells, but considerable suppression was apparent when compared to the transforming effect in cells immortalized by carcinogens. MacAuley and Pawson (35) have also demonstrated that v-src poorly converts early passage rat adrenocortical epithelial cells to anchorageindependent growth.…”
mentioning
confidence: 99%